PARTICIPATORY EXAMINATIONS IN ASYNCHRONOUS LEARNING NETWORKS: LONGITUDINAL EVALUATION RESULTS - Shen, Jia; Bieber, Michael (Online Learning, 2005)
This paper presents longitudinal evaluation results for an online participatory examination process in an information systems course over three semesters. The exam process includes students making up questions, answering other students’ questions, grading answers to questions they author, and appealing the grades. The surveys following each exam elicited students’ feedback, and an experiment compared the participatory exam with the traditional exam in the third semester. Survey results reveal that the majority of students have favorable attitudes towards the participatory exam, and would recommend the participatory examination for future courses. Students in the participatory exam enjoyed the process significantly more than students in the traditional exam, and have higher overall preference for the exam mode, although their perceived learning and perceived fairness in grading are lower than with the traditional exam. Discussion and future research on this topic are also presented.